2021
DOI: 10.26603/001c.25758
|View full text |Cite
|
Sign up to set email alerts
|

The Non-injured Leg Can Be Used as a Reference for the Injured Leg in Single-legged Hop Tests

Abstract: BackgroundSingle-legged hop tests are frequently used in substantiating return to sport decisions following lower extremity injury. Evidence for using the non-injured leg as a reference for the injured leg in the return to sport decision-making at the criterion-based point of return to sport following lower extremity injury is lacking. PurposeTo compare absolute values in single-legged hop tests between the non-injured leg of athletes returning to high-impact sports after lower extremity injury and the matched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…In clinical practice, the contralateral limbs is widely used as a reference of normative value when assessing muscle strength. 33 , 151 , 152 Our results indicate that caution is needed when comparing hamstring strength between limbs in individuals with gradual-onset knee disorders. Deficits in hamstring strength were of medium effect size when compared to pain-free controls, which decreased to small effect size when compared to the unaffected limbs of individuals with knee OA or PFP.…”
Section: Discussionmentioning
confidence: 77%
“…In clinical practice, the contralateral limbs is widely used as a reference of normative value when assessing muscle strength. 33 , 151 , 152 Our results indicate that caution is needed when comparing hamstring strength between limbs in individuals with gradual-onset knee disorders. Deficits in hamstring strength were of medium effect size when compared to pain-free controls, which decreased to small effect size when compared to the unaffected limbs of individuals with knee OA or PFP.…”
Section: Discussionmentioning
confidence: 77%
“…These tests’ frequent usage is partly due to their practical utility and ease of administration [ 4 , 41 ]. The administration of three or four hop tests as the functional component in RTS assessment is common [ 5 , 8 , 42 , 43 , 44 ]. On the other hand, some authors indicated that including all four hop tests as an assessment battery might not be necessary [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…LSI ≥ 90 indicates that performance of the operative leg is ≥ 90% of the non-operative side, generally corresponds to a favorable result, and suggests the patient may be ready to return to sports activity. 16 In addition, the IKCD ratings associated with the KT-1000 stability tests were categorized as normal (0–2 mm), nearly normal (3–5 mm), abnormal (6–10 mm), or severely abnormal (> 10 mm).…”
Section: Methodsmentioning
confidence: 99%